Begonia intermedia, a new species of Begoniaceae from Hainan, China - Tian, Dai-Ke; Li, Chun; Yan, Yue-Hong; Li, Xiang-Peng; Meng, Jing (Phytotaxa, 2014)
Begonia intermedia D.K. Tian & Y.H. Yan, a new species in Begonia sect. Diploclinium (Wright) A. DC (Begoniaceae) from Hainan, China, is described and illustrated. It differs from the morphologically similar B. fimbristipula Hance by its orchid-root-like rhizomes, later flowering and distinctive hairy bracts. Also, based on a molecular phylogenetic analysis, B. intermedia is distinct from B. fimbristipula.